Features of the immune profile and microbiota in persons whose immune status is susceptible or resistant to chronic stress - Lukyanchenko, Oleksandr I; Gozhenko, Olena A; Mel’nyk, Oksana I; Zukow, Walery; Popovych, Igor L (Journal of Education, Health and Sport, 2019)
Background. The presence of influence both sympathetic and vagus links of the autonomic nervous system to the immune system is generally recognized, but the data on their specific immunotropic effects are ambiguous. This includes, in particular, immune responses to the stress-induced shift of sympatho-vagal balance. The purpose of this study is to identify the characteristics of the immune profile, as well as the microbiota associated with it, in persons whose immune status is susceptible or resistant to chronic stress. Materials and Methods. The object of observation were 32 men and 8 women with chronic pyelonephritis in remission. The criterion for inclusion was the magnitude of the sympatho-vagal balance index LF/HF (recorded by "CardioLab+HRV"), which exceeded the age norm by 0,5 σ. Immune status evaluated on a set of I and II levels recommended by the WHO. The observed contingent by pair matching of persons with the same values of LF/HF ratio was retrospectively divided into two groups, almost identical to the average value of LF/HF and its dispersion, but with opposite deviations from the norm of the immune status index. Results. Immune profiles constructed on Z-scores can be divided into three networks. The first set contains 8 parameters (Killing Index vs E. coli and Staph. aur., IL-6, Entropy of LCG, Popovych’s Strain Index of LCG, Igg G and M as well as Microbial Count E. coli) that are not significantly different from persons who are stress-sensitive and stress-resistant. 18 parameters of the second set (Leukocytes, Phagocytose Index vs E. coli and Staph. aur.(PhIA), B-Lymphocytes, Segmented Neutrophils, Microbial Count Staph. aur., T-active (Ta), T-cytolytic and Natural Killers Lymphocytes (NK), IgA, Bactericidity vs E. coli and Staph. aur. (BCA), Bifidobacterium and Lactobacillus feces, Stub Neutrophils, T-helpers, Popovych’s Adaptation Index of LCG (PAI) as well as CIC) to a greater or lesser degree higher in stress-resistant persons. Instead, the 8 parameters of the third set (Lymphocytes, Monocytes and Eosinophils (E), TNF-α, IL-1 as well as Popovych’s Strain Index of LCG, 0-Lymphocytes and Hemolytica E. coli HEC) are higher in stress-sensitive persons. The method of discriminant analysis revealed 9 parameters (ranked by criterion Λ: 0-Lym, BCA, HEC, Ta, CIC, E, PhIA, PAI, NK) that characterize the features of immune profile of stress-susceptible and stress-resistant persons.